COVID-19 pandemic period reflections on problems experienced in distance education at the primary school level: teacher opinions. (8th November 2022) - Omeraga, Nefise Celik; Ozrecberoglu, Nurdan; Genc, Sema Yilmaz; Castanho, Rui Alexandre
The COVID-19 pandemic, which began in December 2019 and quickly spread throughout the world, led to the closure of the world as well as our country and affected all sectors, including the education sector. As a result of the impact of COVID-19, face-to-face education was interrupted all over the world and distance education systems were initiated. During this whole process, various problems occurred in education; consequently, this study aims to investigate the opinions of teachers in primary schools in TRNC working during this time to determine the nature of these problems. Information was gathered using the qualitative research scanning model; for this purpose, an easily accessible sample group selected on a volunteer basis was studied and their views on the subject were determined using a semi-structured interview form. The data obtained from the research were analysed by content analysis.